How Culture Shapes Choices Related to Fertility and Mortality: Causal Evidence at the Swiss Language Border - Lisa Faessler; Rafael Lalive; Charles Efferson (Center for Economic Studies and ifo Institute (CESifo), 2023)
Results from cultural evolutionary theory often suggest that social learning can lead cultural groups to differ markedly in the same environment. Put differently, cultural evolutionary processes can in principle stabilise behavioural differences between groups, which in turn could lead selection pressures to vary across cultural groups. Separating the effects of culture from other confounds, however, is often a daunting, sometimes intractable challenge for the working empiricist. To meet this challenge, we exploit a cultural border dividing Switzerland in ways that are independent of institutional, environmental, and genetic variation. Using a regression discontinuity design, we estimate discontinuities at the border in terms of preferences related to fertility and mortality, the two basic components of genetic fitness. We specifically select six referenda related to health and fertility and analyse differences in the proportion of yes votes across municipalities on the two sides of the border. Our results show multiple discontinuities and thus indicate a potential role of culture to shape preferences and choices related to individual health and fertility. These findings further suggest that at least one of the two groups, in order to uphold its cultural values, has supported policies that could impose fitness costs on individuals in the group.
Keywords: Z10; Z13; D72; I18; 330; gene-culture coevolution; cultural evolution; social learning; cultural variation; fitness; cultural border; regression discontinuity design